MODERNISASI PENDIDIKAN ISLAM DAN RELEVENSINYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA (TELA’AH PEMIKIRAN FAZLUR RAHMAN) - Fathorrahman Fathorrahman; Ervina Zulfa; Joko Andi Koiruman (Reflektika, 2022)
The well-known figure of contemporary Muslim scholar, Fazlur Rahman, is a scientist who seeks to eliminate the dichotomy between modern science and classical Islamic teachings by integrating the two sciences into a complete and complementary unity to form Muslim intelligence who have broad insights and can answer all problems that arise according to the changing times. The researcher was interested in the thinking of this famous Muslim scholar because he was able to overcome various kinds of problems that arise in the world of Islamic education, and the figure of the scholar has given birth to a renewal of Islamic education to be far from stagnant. Researchers researched this modernist scientist to find the relevance between the idea of modernization of education presented by Fazlur Rahman and today's modernization of education in Indonesia. This type of research is library research, with a qualitative descriptive approach, a research method that intends to describe as a whole and critically social reality and various events that occur in society. The results found by the researcher after conducting this analysis contain the conclusion that there is relevance between the concept of modernization of Islamic education from Fazlur Rahman's perspective and the modernization of Islamic education in Indonesia, both regarding efforts to modernize Islamic education, goals, strategies and methods, criteria for educators and students, Islamic education systems and facilities, as well as critical thinking in dealing with problems that arise among humankind.